The Buddhist Attitude towards Loss: Integrating Noble Eightfold Path as Therapy for Coping with Loss - Tri Saputra Medhacitto; Suranto; Sukodoyo; Sanu Mahatthanadull (Jounal Nyanadassana, 2026)
This research aims to explore the Buddhist attitude towards loss and to examine the integration of Noble Eightfold Path as therapy for coping with loss. This research adopts library approach conducted using content analysis as the primary method for data interpretation. Following Miles and Huberman’s analytical model, the process consists of four stages: data collection, data reduction, data display, and drawing and verifying conclusions. Data were collected from both primary sources, including the Pali Canon and its commentaries, and secondary sources, such as scholarly books and journal articles accessed via Google Scholar. The research findings revealed that: 1) Loss and separation from the loved one are inevitable experiences of human life, and Buddhism considers it as a kind of suffering (piyehi vippayogo dukkho); 2) The Buddha identified the path leading to cessation of this suffering is through Noble Eightfold Path, consisting right view (sammādiṭṭhi), right thought (sammāsaṅkappo), right speech (sammāvācā), right action (sammākammanto), right livelihood (sammāājīvo), right effort (sammāvāyāmo), right mindfulness (sammāsati) and right concentration (sammāsamādhi). The path is called as Middle Way (majjhimā paṭipadā), avoiding two extreme practices: self-mortification and sensual-indulgence. This teaching is effective in reducing the risk of self-indulgence and self-destructive behavior caused by emotional turmoil when facing loss. The Noble Eightfold Path (ariya atthaṅgika magga) can be used as a way for coping with loss, presenting the way to adopt the proper attitude when facing the loss and to manage the negative emotions.